Comparison of Fentanyl-Propofol and Ketamine-Propofol Combination in Induction and Maintenance with Intravenous Anesthesia for Short Surgical Procedures at Moderate Elevations - Bhattarai, Ramesh; Hamal, Pawan Kumar (Journal of Nepal Health Research Council, 2021)
Background: The aim of the study is to evaluate the efficacy of Ketamine-Propofol compared to Fentanyl-Propofol combination during induction and maintenance of total intravenous anesthesia for short surgical procedures at moderate elevation. Methods: A prospective pilot study was done comparing between Fentanyl (1.2 mcg/kg)- Propofol and Ketamine (0.5mg/kg)-Propofol with 30 in each group at moderate altitude of approximately 2514 meters for the requirement of positive pressure ventilation, changes in heart rate and mean arterial pressure intraoperatively, total Propofol consumption and time to attain Modified Steward Score of 6.Results: Requirement for positive pressure ventilation was significantly high in Fentanyl-Propofol group 18 (60%) compared to Ketamine-Propofol 1 (0.03%) [P = 0.00]. Fall in oxygen saturation was significant at 2 minute of Ketamine or Fentanyl [95% CI, 3.10-5.76, P = 0.00], after induction with Propofol [95% CI, 2.30-4.03, P = 0.00], 5 minute [95% CI, 1.66-3.54, P = 0.00], 10 minutes [95% CI, 0.55-2.32, P = 0.02], 15 minutes [95% CI, 0.50-2.09, P = 0.00] and 20 minutes [95% CI, 0.43-2.23, P = 0.00] respectively after study drug between the groups. Total Propofol consumption was significantly higher [95% CI, 0.19-0.43, P = 0.00] in KP (1.55±0.27mg/kg) compared to FP (1.23±0.16 mg/kg). Conclusions: At moderate elevations of 2514 meters, during the induction and maintenance of intravenous anesthesia, Ketamine-Propofol causes significantly less fall in oxygen saturation in the first 20 minutes requiring lesser need of positive pressure ventilation with comparable least fall in heart rate and mean arterial pressure with higher total Propofol consumption when compared to Fentanyl-Propofol. It took a significantly longer time to recovery with Modified steward score of maximum 6 with Ketamine-Propofol.Keywords: Fentanyl; intravenous anesthesia; ketamine; moderate altitude; propofol